Unmasking the Area Postrema on MRI: Utility of 3D FLAIR, 3D-T2, and 3D-DIR Sequences in a Case–Control Study - Javier Lara-García; Jessica Romo-Martínez; Jonathan Javier De-La-Cruz-Cisneros; Marco Antonio Olvera-Olvera; Luis Jesús Márquez-Bejarano (Journal of Imaging)
The area postrema (AP) is a key circumventricular organ involved in the regulation of autonomic functions. Accurate identification of the AP via MRI is essential in neuroimaging but it is challenging. This study evaluated 3D FSE Cube T2WI, 3D FSE Cube FLAIR, and 3D DIR sequences to improve AP detection in patients with and without multiple sclerosis (MS). A case–control study included 35 patients with MS and 35 with other non-demyelinating central nervous system diseases (ND-CNSD). MRI images were acquired employing 3D DIR, 3D FSE Cube FLAIR, and 3D FSE Cube T2WI sequences. The evaluation of AP was conducted using a 3-point scale. Statistical analysis was performed with the chi-square test used to assess group homogeneity and differences between sequences. No significant differences were found in the visualization of the AP between the MS and ND-CNSD groups across the sequences or planes. The AP was not visible in 27.6% of the 3D FSE Cube T2WI sequences, while it was visualized in 99% of the 3D FSE Cube FLAIR sequences and 100% of the 3D DIR sequences. The 3D DIR sequence showed superior performance in identifying the AP.